Modo reprodutivo de acessos de Paspalum spp. (grupo informal Plicatula) e busca de marcadores moleculares associados a apomixia - Gonçalves, Tiago Maretti (Universidade Federal de São Carlos, 2019)
Belonging to the grass family, the genus Paspalum has more than 350 species, many of them with great forage potential or for use as vegetation. The Paspalum Germplasm Bank (GB) of Embrapa Pecuária Sudeste enables research with the genus and currently has about 450 accessions of 50 species, most of them belonging to the Plicatula group. Many of the Paspalum accessions of this group are tetraploid (2n = 4x = 40) and of apomitic behavior, and sexual genotypes are rare. Identifying only accessions with apomitic reproduction mode in a collection limits the breeding program because there is no possibility of hybridization. To circumvent this situation, diploid and sexual genotypes must be polyploidized for use in intra and interspecific crosses. Thus, reproductive characterization in Paspalum is of great importance, since it enables the identification of sexual genotypes and facilitates the choice of potential parents for genetic improvement. In this context, the objective of the present work was to reproductively characterize 137 Paspalum accessions belonging to the informal Plicatula group conserved in the Paspalum GB of Embrapa Pecuária Sudeste by the use of flow cytometry and cytoembriological analysis and search for molecular markers associated to apomixis. After analysis of the data obtained by flow cytometry, 49 accessions were considered highly apomictic, 85 were facultative apomictics and one accession (BGP 272 - P. rojasii) showed behavior compatible with the sexual reproductive mode. In addition to these results, the flow cytometry technique made it possible for the first time to characterize the reproductive mode of 12 accessions belonging to P. rhodopedum species. By cytoembriological analysis, five accessions were characterized, three sexual accessions (BGP 281 - P. lenticulare; BGP 272 - P. rojasii and BGP 380 - P. compressifolium) and two accessions (BGP 232 - P. plicatulum; BGP 178 - P. compressifolium) characterized as highly apomictic and facultative apomictic, respectively. In the molecular part, an association for apomixis was sought with the use of 1 marker p779/780, described as completely linked to apporia in B. decumbens, two RAPD (Random Amplified Polymorphic DNA) and 19 SCAR (Sequence Characterized Amplified Region) previously associated with apomixis in the genus Paspalum and, based on the Bulk Segregant Analysis methodology, 51 nuclear microsatellite markers were genotyped, totaling 73 molecular markers evaluated in P. compressifolium and P. lenticulare sexual and apomitic accessions. For SCAR markers, accessions belonging to P. rojasii were also included. A large polymorphism occurred between the samples, but no link was observed between the apomixis characteristic and the molecular markers evaluated. The present study shows a greater reproductive genetic variation among the characterized accessions, there was a correspondence between the ploidy level and the reproduction mode, as expected, and none of the genotyped molecular markers were linked to apospory in the evaluated germplasm. Thus, this study presented important results that could be applied to the selection of parents in Paspalum breeding programs.
Reproductive mode of Paspalum spp. access (Plicatula informal group) and search for molecular markers associated with apomixis
Keywords: Citometria de fluxo; Análise citoembriológica; Gramíneas; Germoplasma; Pré-melhoramento; Flow cytometry; Cytoembriological analysis; Grasses; Germoplasm; Pre-breeding; CIENCIAS BIOLOGICAS::GENETICA::GENETICA VEGETAL